Worldmark encyclopedia of the nations (Thomson Gale, 2007)
Contains over two hundred articles that examine the history, economy, society, culture, and politics of the world's countries and dependencies, providing information in more than forty categories, and features an in-depth look at the United Nations system and the organization's related agencies.